PEMODELAN LOYALITAS PENGGUNA APLIKASI OVO DI KOTA MALANG: PERAN KUALITAS LAYANAN DAN CITRA MEREK DENGAN KEPUASAN SEBAGAI PEMEDIASI - Kumala, Imtinan Widhah; Saefudin, Saefudin; Adibatunabillah, Suko Rina (JURNAL MANAJEMEN DAKWAH, 2023)
The increasing number of e-money users makes business competition in the industry increasingly tight. This has an impact on decreasing the number of users on the OVO application. This research aims to analyze the influence of service quality and brand image on loyalty among OVO users in Malang City with user satisfaction as a mediating variable. This research is causality research with sampling using a purposive sampling approach. The number of samples that met the criteria was 303 respondents who were OVO users in Malang City. Data analysis was tested statistically via AMOS with the criteria P-Value ≤ 0.05. The research results prove that service quality and brand image partially have a significant effect on user satisfaction and loyalty. User satisfaction has been proven to have a significant effect on user loyalty. Mediationally, the research results prove that satisfaction is able to mediate the relationship between service quality and user loyalty. Furthermore, satisfaction is able to mediate the relationship between brand image and user loyalty.